Ablation-resistant carbide Zr0.8Ti0.2C0.74B0.26 for oxidizing environments up to 3,000 °C - Yi Zeng (Nature Portfolio, 2017)
Hypersonic and aerospace applications motivate development of materials with improved resistance against ablation and oxidation at high temperatures. Here authors demonstrate a quaternary carbide, where sealing by surface oxides, slow oxygen diffusion and a graded structure yield improved ablation resistance over established ceramics.